Degree in Artistic and Cultural Mediation (ESELx - IPL): a critical analysis on the role of the mediator and mediation process in the Portuguese context - Cruz,Cristina Barroso (2021)
Abstract The changes in the dynamics of the cultural sector in Portugal are increasingly evident creating a growing need to bring artists and cultural producers closer to the public. However, few professionals can develop this type of work resorting to a solid theoretical and technical background. These needs led to the creation of the degree in Artistic and Cultural Mediation in the 2016-2017 school year, at the Lisbon School of Education (Polytechnic Institute). This undergraduate program aims to train professionals who can establish a relationship between cultural producers and the public by developing work strategies effective in hybrid territories that combine different but complementary features such as education, programming, creative and artistic processes, assuming their integrative role. After the graduation of the first students, it is important to reflect on the several aspects that influence the development of this degree and what is its contribution to cultural democracy and democratization in Portugal.